A medication workshop for patients with schizophrenia living in community care homes. Issue 1 (13th December 2012) - Perry, Jennifer; Bashir, Khaver; Lingwood, Susie
Abstract: Psychoeducation for patients with schizophrenia can improve a range of outcomes. Our aim was to test a workshop intervention enabling service users to learn more about mental illness and their medication. A Quality Improvement Project was undertaken to create a workshop for patients with a diagnosis of schizophrenia within the Haringey Community Rehabilitation Team (HCRT) . The response was tested using anonymous questionnaires after each workshop. We held ten workshops (total of 47 participants), after which 83% of patients felt that the workshop had helped them to understand more about their mental health, 77% felt they were able to understand the purpose of their medication, 79% felt they were able to understand the side effects, and 70% felt they could have a say in prescribing. Objectives for the Quality Improvement Project were met. This workshop will be used for other patients within the HCRT and is transferable to other community mental health teams.